Intense magmatic degassing through the lake of Copahue volcano, 2013–2014. Issue 9 (14th September 2015) - Tamburello, G.; Agusto, M.; Caselli, A.; Tassi, F.; Vaselli, O.; Calabrese, S.; Rouwet, D.; Capaccioni, B.; Di Napoli, R.; Cardellini, C.; Chiodini, G.; Bitetto, M.; et al.
Abstract: Here we report on the first assessment of volatile fluxes from the hyperacid crater lake hosted within the summit crater of Copahue, a very active volcano on the Argentina‐Chile border. Our observations were performed using a variety of in situ and remote sensing techniques during field campaigns in March 2013, when the crater hosted an active fumarole field, and in March 2014, when an acidic volcanic lake covered the fumarole field. In the latter campaign, we found that 566 to 1373 t d −1 of SO2 were being emitted from the lake in a plume that appeared largely invisible. This, combined with our derived bulk plume composition, was converted into flux of other volcanic species (H2 O ~ 10989 t d −1, CO2  ~ 638 t d −1, HCl ~ 66 t d −1, H2  ~ 3.3 t d −1, and HBr ~ 0.05 t d −1 ). These levels of degassing, comparable to those seen at many open‐vent degassing arc volcanoes, were surprisingly high for a volcano hosting a crater lake. Copahue's unusual degassing regime was also confirmed by the chemical composition of the plume that, although issuing from a hot (65°C) lake, preserves a close‐to‐magmatic signature. EQ3/6 models of gas‐water‐rock interaction in the lake were able to match observed compositions and demonstrated that magmatic gases emitted to the atmosphere were virtually unaffected by scrubbing of soluble (S and Cl) species. Finally, the derived large H2 O flux (10, 988 t d −1 ) suggested a mechanism in which magmatic gas stripping drove enhanced lake water evaporation, a process likely common to many degassing volcanic lakes worldwide. Key Points: First volatile flux record of crater lake gas emissions from Copahue volcano Magmatic gases breaching through the lake surface Magmatic gas stripping drive enhanced lake water evaporation